Mechanism to motivate information sharing behavior on the BIM platform for construction projects - Xiaowei An; Sicheng Ren; Hanxiao Liang (Journal of Asian Architecture and Building Engineering)
The full realization of building information modeling (BIM) value requires multi-party collaborative application of the BIM platform. The effective application of the BIM platform requires all parties involved in construction projects to share information and data. However, contractors are reluctant to provide key information to BIM platforms without receiving any incentive. Employing the principal-agent theory and incentive theory, from the perspective of the owner, this study proposes an information sharing incentive model for the BIM platform. The model was verified by numerical simulation and a case study. The results of the study found that, with incentive mechanisms, contractors were willing to provide information to the BIM platform. And through the effective application of information provided by contractors to the BIM platform, the project could realize added-value so as to improve project benefits. The research results of this paper are beneficial to improve the theories related to BIM collaborative application and BIM platform management, and can provide support for the construction of information sharing incentive mechanism of BIM platform for owners.